Weeding Frequencies Improve Soil Available Nitrogen in Organic Paddy Field - Maimunah, Margi Asih; Kautsar, Valensi; Bimantara, Putu Oki; Kimani, Samuel Munyaka; Utami, Asih Indah; Sabri, Riza Kurnia; Tawaraya, Keitaro; Utami, Sri Nuryani Hidayah; Purwanto, Benito Heru; Cheng, Weiguo (PLANTA TROPIKA, 2022)
Appropriate weeds control is needed against weeds constraints in field, especially the organic field. With the appropriate management, weeding would benefit the organic field not only in reducing weeds but also in increasing nitrogen (N) availability in organic rice fields. This research aims to observe soil available N changes affected by weeding frequencies in organic paddy fields. Treatments applied were five weeding frequencies (WF) such as 0 WF, 2 WF, 4 WF, 6 WF, and 8 WF, to study the effect of various weeding frequencies on soil total N and available N ( NH4+ and NO3–) in the organic rice field. The soil in the conventional field was analyzed as a comparison to organic field soil. The results showed that soil C and N contents are similar in all treatments. Meanwhile, 6 WF performed the highest soil  NH4+ among organic plots (10.36 mg N kg–1) and 8 WF enhanced soil NO3– to the highest average among all plots (10.12 mg N kg–1). The treatment of 6 WF and 8 WF also maintain the increase of soil  NH4+ to 51 days after transplanting (DAT), meanwhile 0 WF, 2 WF, and 4 WF decreased after 40 DAT. Water samples from fields inlet-outlet and river showed that  NH4+ content found in water sample was higher than NO3–. We concluded that the more frequencies of weeding applied to organic fields potentially preserved soil inorganic N longer, which is very important in supporting rice growth.